The scarcity of industrial designs register that come from fashion in Pernambuco (Research, Society and Development, 2021)
Objective: to analyse the dissemination of industrial designs protection that derives from the professional practices of the fashion designer in institutions that foster emerging companies of creative economy in the graduation of Design and Fashion design from Pernambuco. Materials and Methods: it was delimited as an applied, qualitative, exploratory, bibliographic and documental study. The time cutting was the last 5 years (2016 – 2020).  It was analysed 2 pedagogical projects of bachelor courses in Design that there are fashion disciplines and 5 Technological courses of Fashion design. It was shown professional points of support and development to original fashion brands and there were 5 events of dissemination of Intellectual Property. Results: there was a scarcity of events that address the protection of industrial designs asset to original fashion brands, and still the lack of these contents in graduation courses.